Conquistando a Paraíba: o ensino de História através dos jogos - Figueiredo Júnior, Emílio Pinto de (2024)
The incorporation of games and gamification in the classroom emerges as a significant methodological approach for teaching history, providing an enriching and engaging experience for students. This study aims to assess the effectiveness of these tools by utilizing the context of the conquest of Paraíba as a basis to rescue the rich local history, often neglected due to several factors. To achieve this goal, it was decided to adopt the content gamification methodology, involving the use of gaming elements as an educational strategy to infuse a playful and interactive aspect into history learning. and the application of webquests, which are structured online activities designed for researching and exploring specific themes. The learning mediator solution created from this methodology aims to strengthen the discussion and expand the possibilities of more engaging history teaching, in which students can connect in a meaningful way with the past and understand the importance of local historical events for the formation of current society.